2019
DOI: 10.1111/1755-0998.13119
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure in the “Plastisphere”: Molecular resources for imaging microscopic communities on plastic marine debris

Abstract: Plastic marine debris (PMD) affects spatial scales of life from microbes to whales.However, understanding interactions between plastic and microbes in the "Plastisphere"-the thin layer of life on the surface of PMD-has been technologylimited. Research into microbe-microbe and microbe-substrate interactions requires knowledge of community phylogenetic composition but also tools to visualize spatial distributions of intact microbial biofilm communities. We developed a CLASI-FISH (combinatorial labelling and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 64 publications
2
61
0
Order By: Relevance
“…The spatial distribution of microorganisms in microplastic biofilms, as in other biofilms, is generally not random or homogeneous. Heterogeneous bacterial communities were observed around phytoplankton and bryozoan structures, which may be due to associations arising from the preferential attraction of bacteria to exuded organic matter and other nutrients by phytoplankton and hydrodynamic effects caused by the shape and structure of surface layers (Schlundt et al 2019 ). Exopolysaccharides were found to play an important role in the formation of hetero-aggregates between microalgae and microplastics (Lagarde et al 2016 ).…”
Section: Microbial Communities Of Microplastic Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution of microorganisms in microplastic biofilms, as in other biofilms, is generally not random or homogeneous. Heterogeneous bacterial communities were observed around phytoplankton and bryozoan structures, which may be due to associations arising from the preferential attraction of bacteria to exuded organic matter and other nutrients by phytoplankton and hydrodynamic effects caused by the shape and structure of surface layers (Schlundt et al 2019 ). Exopolysaccharides were found to play an important role in the formation of hetero-aggregates between microalgae and microplastics (Lagarde et al 2016 ).…”
Section: Microbial Communities Of Microplastic Biofilmsmentioning
confidence: 99%
“…Exopolysaccharides were found to play an important role in the formation of hetero-aggregates between microalgae and microplastics (Lagarde et al 2016 ). However, microbe-microbe and microbe-substratum interactions in microplastic biofilms and their environmental significance remain largely unknown (Amaral-Zettler et al 2020 ; Schlundt et al 2019 ). Correlative network analyses based on 16S rDNA amplicon and metagenomic data indicated that key bacterial genera (e.g.…”
Section: Microbial Communities Of Microplastic Biofilmsmentioning
confidence: 99%
“…CLASI‐FISH and microbial ecology applications in the Plastisphere demonstrated with samples from the Atlantic Ocean by Schlundt et al. (2020). The application of spectral imaging in FISH improves the number of bacterial groups that can be visualized on plastic marine debris simultaneously, compared with other FISH methods (e.g., CARD‐FISH), and including different levels of taxonomic resolution (above; bacteria represented in colours).…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, perhaps one of the most attractive results presented by Schlundt et al. (2020) is the visualization of bacteria and phytoplankton together and across time. Previous scanning electron microscopy on microplastics in the ocean has indicated the importance of diatoms in the early biofouling of the plastic marine debris, but with a low taxonomic resolution for the bacterial groups associated with them (Reisser et al., 2014).…”
Section: Figurementioning
confidence: 99%
“…This included metatranscriptomics to determine the composition and function of complex microbial communities, specifically as it was applied to blood parasites in birds (Galen et al., 2020; Perspective by Cassin‐Sackett, 2020). Novel methods were highlighted, including a new approach for visualizing microbial communities on marine plastic debris using specialized probes (Schlundt et al, 2019; Perspective by Arias‐Andres, 2020) and improved analyses of polyploids in landscape genomics (Meirmans, 2020; Perspective by Ackiss & Balao, 2020). A comparison of double‐digest RADseq de novo assembly software (LaCava et al., 2020; Perspective by Marrano et al., 2020) was published that assists researchers to navigate across available software programs.…”
Section: Associate Editors and Reviewersmentioning
confidence: 99%